Third Ventricle Enlargement in Neonates with Trisomy 21 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Measurements of routine head sonographic scans of 57 term infants with trisomy 21 born between 2000 and 2005 were performed within 7 days after birth and were compared with scans of 21 randomly selected, healthy, term infants without trisomy 21 at Shaare Zedek Medical Center, Jerusalem; Ben Gurion University of the Negev, Beer Sheva; and Hadassah University Hospital, Jerusalem, Israel.